Comparing the Impact of Nature, Blended, and Traditional Preschools on Children’s Resilience: Some Nature May Be Better Than None - Ernst, Julie; Juckett, Hannah; Sobel, David (Frontiers in Psychology, 2021)
This study examined the effect of nature preschools on the development of key protective factors associated with psychological resilience. The Deveraux Early Childhood Assessment for Preschoolers, Second Edition (DECA-P2) was used to assess the growth in the protective factors of initiative, self-regulation, and attachment in 87 children who attended nature, blended, and traditional preschool classes within the same school district. Study results suggest nature preschool participation was important in the context of initiative. Blended classes, where some nature-based practices were incorporated into traditional preschool classes, were sufficient in the sense of being more impactful than traditional classes on self-regulation, attachment, and the total protective factors overall. Implications are discussed within the context of the limitations of the study.